The Governance of the ReFi Ecosystem: Integrity in Voluntary Carbon Markets as a Common Resource - Andres Diaz-Valdivia; Marta Poblet-Balcell (International Journal of the Commons)
Addressing the shortcomings of the Voluntary Carbon Markets (VCMs), a nascent blockchain industry has disrupted this area with an ever-growing number of projects leveraging open-source, decentralised base-layer platforms (e.g. Ethereum, Cosmos) and business-oriented decentralized applications (Dapps). Building on this emerging digital infrastructure over the Internet, community-driven decentralized autonomous organizations (DAOs) are building new socio-technical systems for decentralized finance (DeFi) and, more recently, regenerative finance (ReFi). Both areas are making their way into VCMs promising improved transparency, efficiency and greater accessibility. This paper examines the goals, scope, and intended outcomes of prominent blockchain-based ReFi projects in the VCM space. In particular, it explores the potential for commons-based outcomes emerging from peer-to-peer configurations in the VCM. Using a qualitative approach, the study analyses text-data from industry whitepapers focusing on the cases of Celo, Regen, Toucan, Klima and Moss. The findings show the ReFi ecosystem as a low-transaction-cost environment fostering open-source prototypes of peer-production for carbon accounting and trading. These innovations materialize through application interfaces operating on base-layer blockchains running smart-contracts and tokens. The tokenization of real-world assets (RWA) or rights (e.g. renewable energy generation, storage capacity, or forestry land) and the automation of operations (e.g. exchanges) via smart contracting, provides participants with new affordances for secure, bi-directional coordination in near-real time. The preliminary conclusion is that, while the ReFi organizations considered seem to be Ostrom-compliant with regard to some principles (e.g. clearly defined boundaries, procedures for making own rules, monitoring, or minimal recognition of rights) others are still ad-hoc practices or work in progress (e.g. graduated sanctions or dispute resolution mechanisms). This study contributes to the critical exploration of enhanced governance mechanisms, enabled by technological innovation, that can address climate action challenges and provide viable alternatives to traditional market-based approaches.